Lactic acid bacteria: beyond fermentation to bio-protection against fungal spoilage and mycotoxins in food systems - Rahman, Md Saifur; Soltani, Samira; LaPointe, Gisèle; Karboune, Salwa; Fliss, Ismail (Frontiers in Microbiology, 2025)
Recent outbreaks of foodborne diseases have highlighted the challenges of maintaining food safety, emphasizing the need for effective strategies to control pathogens and spoilage organisms. Toxins produced by indigenous fungi pose serious economic issues and undermine food security. Mycotoxin spoilage is a ubiquitous hazard that affects all food commodities; however, bakery products, dairy, fruits, vegetables, and meat are particularly vulnerable. The quality of food is perceived through senses such as taste, aroma, and texture. These sensory attributes significantly impact the overall sensation of the product and determine whether it will be accepted or rejected by consumers. Spoilage not only reduces consumer satisfaction but also drastically shortens the shelf life of food. This review highlights the ability of Lactic Acid Bacteria (LABs) to produce diverse antimicrobials, emphasizing antifungal metabolites as effective tools for enhancing food preservation and extending shelf life. As consumer demand for ‘clean label’ solutions increases, these natural antimicrobials promise safe and effective alternatives for enhancing food safety, reducing fungal spoilage, and extending shelf life of various perishable food commodities and reducing economic losses.